Gelatin from red tilapia (Oreochromis spp.) scales: Optimization of its extraction and detailed characterization of its chemical and viscoelastic properties - Jairo Andrés Camaño Echavarría; Amine Nekkaa; Philippe Arnoux; Christelle Mathé; Céline Cakir-Kiefer; Loïc Stefan; Cédric Paris; Katalin Selmeczi; José Edgar Zapata Montoya; Laetitia Canabady-Rochelle (Applied Food Research)
Gelatin is widely used in food and pharmaceutical industries for its functional and bioactive properties. When extracted from fish by-products, the environmental impacts of these former waste are reduced. This study aimed to optimize the gelatin extraction from red tilapia scales using a fractional factorial design and evaluate its physicochemical and viscoelastic properties. The effects of solvent-to-solid ratio (2–10 mL/g), extraction time (1–3 h), temperature (65–85 °C) and ultrasound (0–60 min) were investigated on the crude protein content (CPC), the free amino groups (FAG) and the protein extraction yield (PEY). The CPC extracted (95.4–99.2 %) was in agreement with protein isolates (>85 %) and the extraction time and temperature had a significant positive effect on FAG and PEY. Extraction conditions after optimization were: 10 mL/g solvent-to-solid ratio, 3 h, 85 °C, and without ultrasounds. Gelatin obtained under optimal condition improved highly the protein extraction and exhibited the best molecular weight distribution profile (α1/α2 chain ratios: 1.7) to offer suitable viscoelastic properties in term of gelling (18 °C) and melting capacities (25.8 °C). This finding highlights the important potential of such natural protein source as a tailored gel for food or cosmetic formulations.Abbreviations: AA, Amino acid; Adeq precision, Adequate precision; AAA, Aromatic amino acids; ANOVA, Analysis of variance; BCAA, Branched chain amino acids; CD, Circular dichroism spectroscopy; CPC, Crude protein content; EAA, Essential amino acids; FAG, Free amino group; FFD, Fractional factorial design; FTIR, Fourier-transform infrared spectroscopy; G′, Storage modulus, G′′, Loss modulus; HAA, Hydrophobic amino acids; LMWA, Low molecular weight aggregates; M, Protein marker, NCAA, Negatively charged amino acids; PCAA, Positively charged amino acids; PEY, Protein extraction yield; OPA, o-phthalaldehyde; SDS-PAGE, Sodium dodecyl sulfate polyacrylamide gel electrophoresis; TSF, tilapia scale flour; TSG, tilapia scale gelatin.